Age And Effective Human Resource Management - Florahi, Oluoch Mercy (European Scientific Journal, ESJ, 2019)
This article examines the implications of an aging workforce for human resource management (HRM). It first looks at the theories relevant to understanding age-related changes at work, including lifespan development theories, changes in work outcomes, and the social context for age (e.g., age stereotyping). Drawing from social-identity theory, human capital theory, role theory, jobs demand theory, relational demographic theory and social conservation of resource theory, theoretically the argument is that, in agediverse companies, age-based subgrouping processes occur, favoring a shared perception of a negative age-discrimination climate. This perceived negative age-discrimination climate in turn negatively relates to organizational performance. It then considers the ways that organizations can keep their employees—including those who are aging—satisfied, engaged, productive, and healthy in their jobs in terms of traditional HR practices like recruitment and selection, training, and occupational safety and health and implications of age in human resource decisions.